Business intelligence strategy and big data analytics : a general management perspective - Williams, Steve; ScienceDirect eBooks (Cambridge, MA : Morgan Kaufmann is an imprint of Elsevier, 2016)
Including exercises and case studies with road-tested advice, this book provides ideas for improving the business performance of one$1 (Bs company or business functions, and emphasizes proven, practical, step-by-step methods that readers can readily apply in their companies. --s
Includes bibliographical references and index.
Safari Books Online
Elsevier
Keywords: Business intelligence; Big data; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Big data; Business intelligence; Electronic books